Correlations between supermassive black holes and hot gas atmospheres in IllustrisTNG and X-ray observations. Issue 2 (18th December 2020) - Truong, Nhut; Pillepich, Annalisa; Werner, Norbert
ABSTRACT: Recent X-ray observations have revealed remarkable correlations between the masses of central supermassive black holes (SMBHs) and the X-ray properties of the hot atmospheres permeating their host galaxies, thereby indicating the crucial role of the atmospheric gas in tracing SMBH growth in the high-mass regime. We examine this topic theoretically using the IllustrisTNG cosmological simulations and provide insights to the nature of this SMBH – gaseous halo connection. By carrying out a mock X-ray analysis for a mass-selected sample of TNG100 simulated galaxies at $z$ = 0, we inspect the relationship between the masses of SMBHs and the hot gas temperatures and luminosities at various spatial and halo scales – from galactic (∼ R e ) to group/cluster scales (∼ R 500c ). We find strong SMBH-X-ray correlations mostly in quenched galaxies and find that the correlations become stronger and tighter at larger radii. Critically, the X-ray temperature ( k B T X ) at large radii ( r ≳ 5 R e ) traces the SMBH mass with a remarkably small scatter (∼0.2 dex). The relations emerging from IllustrisTNG are broadly consistent with those obtained from recent X-ray observations. Overall, our analysis suggests that, within the framework of IllustrisTNG, the present-time M BH – k B T X correlations at the high-mass end ( M BH ≳ 10 8 M ⊙ ) are fundamentally a reflection of the SMBH mass–halo mass relation, which at such high masses is set by the hierarchical assembly of structures. The exact form, locus, and scatter of those scaling relations are, however, sensitive to feedback processes such as those driven by star formation and SMBH activity.